2012
DOI: 10.1111/j.1525-1470.2012.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lymphatic Malformation (Gorham‐Stout) of the Pelvis with Prominent Skin Involvement

Abstract: Gorham-Stout syndrome is a rare disease characterized by progressive osteolysis leading to disappearance of the bone. Vascular proliferations have been implicated in the pathogenesis of this syndrome. The case of a 7-year-old girl with a prominent invasive lymphatic malformation on the lumbosacral area and massive osteolysis of the pelvic girdle is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
0
8
0
2
Order By: Relevance
“…Osteoclasts have been detected in many different GSD patient samples ( Pazzaglia et al, 1997 ; Avelar et al, 2010 ; Bruder et al, 2009 ; Choma et al, 1987 ; Hammer et al, 2005 ; Hirayama et al, 2001 ; Lehmann et al, 2009 ; Möller et al, 1999 ; Silva, 2011 ; Spieth et al, 1997 ; Poirier, 1968 ; Jones et al, 1958 ) and CTX-1 has been reported to be elevated in several patients ( Liu et al, 2016 ). Zoledronic acid has been given to GSD patients in an attempt to prevent bone loss ( Avelar et al, 2010 ; Hagendoorn et al, 2006 ; Kuriyama et al, 2010 ; Leite et al, 2013 ; Ruggieri et al, 2011 ; Gem et al, 2014 ; Mignogna et al, 2005 ; Yerganyan et al, 2015 ). Indeed, several case reports state that there is no further progression of the disease after the patient is treated with zoledronic acid ( Avelar et al, 2010 ; Kuriyama et al, 2010 ; Gem et al, 2014 ; Mignogna et al, 2005 ; Yerganyan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts have been detected in many different GSD patient samples ( Pazzaglia et al, 1997 ; Avelar et al, 2010 ; Bruder et al, 2009 ; Choma et al, 1987 ; Hammer et al, 2005 ; Hirayama et al, 2001 ; Lehmann et al, 2009 ; Möller et al, 1999 ; Silva, 2011 ; Spieth et al, 1997 ; Poirier, 1968 ; Jones et al, 1958 ) and CTX-1 has been reported to be elevated in several patients ( Liu et al, 2016 ). Zoledronic acid has been given to GSD patients in an attempt to prevent bone loss ( Avelar et al, 2010 ; Hagendoorn et al, 2006 ; Kuriyama et al, 2010 ; Leite et al, 2013 ; Ruggieri et al, 2011 ; Gem et al, 2014 ; Mignogna et al, 2005 ; Yerganyan et al, 2015 ). Indeed, several case reports state that there is no further progression of the disease after the patient is treated with zoledronic acid ( Avelar et al, 2010 ; Kuriyama et al, 2010 ; Gem et al, 2014 ; Mignogna et al, 2005 ; Yerganyan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…L'approche médicale permet dans un certain nombre de cas de stabiliser la maladie. Les traitements qui ont été utilisés dans la littérature sont l'interferon alpha 2b [24][25][26] et les biphosphonates par voie orale (clodronate, alendronate) ou veineuse (pamidronate, acide zolédronique) [11,26,27]. Il est très difficile d'avoir une idée claire de l'attitude à adopter vu l'hétérogénéité des schémas dans la littérature, la…”
Section: Traitement Systémiqueunclassified
“…Стабилизацию и реконструкцию пораженных сегментов скелета реко-мендуют проводить в стабильной фазе болезни [20]. Лучевую терапию при-меняют как в виде монотерапии, так и в комплексе с хирургическим лече-нием [8,9,11], указывая на ее клини-ческую эффективность в 75 % случа-ев локальных поражений при общей дозе облучения 36-45 Гр фракциями по 2 Гр [8,9,33,35]. Из медикаментоз-ных средств используют бисфосфо-наты и интерферон-альфа-2в, причем как изолированно, так и совместно [1,15,16,18,25,31,42,54].…”
Section: рисunclassified